A genetically encoded multifunctional unnatural amino acid for versatile protein manipulations in living cells. Issue 12 (15th August 2016) - Ge, Yun; Fan, Xinyuan; Chen, Peng R.
Abstract : A multifunctional UAA, PABK, is developed for diverse protein manipulation purposes, especially protein activation in living cells. Abstract : The genetic code expansion strategy allowed incorporation of unnatural amino acids (UAAs) bearing diverse functional groups into proteins, providing a powerful toolkit for protein manipulation in living cells. We report a multifunctional UAA, N ε - p -azidobenzyloxycarbonyl lysine (PABK), that possesses a panel of unique properties capable of fulfilling various protein manipulation purposes. In addition to being used as a bioorthogonal ligation handle, an infrared probe and a photo-affinity reagent, PABK was shown to be chemically decaged by trans -cyclooctenols via a strain-promoted 1, 3-dipolar cycloaddition, which provides a new bioorthogonal cleavage strategy for intracellular protein activation. The biocompatibility and efficiency of this method were demonstrated by decaging of a PABK-caged firefly luciferase under living conditions. We further extended this method to chemically rescue a bacterial toxin OspF inside mammalian host cells.